RANCANG BANGUN PENGONTROL GERAKAN ROBOT OPENMANIPULATOR DENGAN MATLAB - Winarta, Daniel Kelvin; Widodo, Romy Budhi; Subianto, Mochamad (Ma Chung Press, Universitas Ma Chung, 2024)
With the advancement of science, society demands industry to make a product with good quality and produced in a short time. Because of this demand, many industries have switched from manual production processes to automated production processes so that the products produced have consistent quality and are quickly produced. One of the most widely used technologies today is the robot arm. This study aims to create a robot arm motion control application using the MATLAB application. The robot arm used consists of several devices, namely the U2D2 board, power adapter, and servo dynamixel. Prototype testing is carried out by moving the position of the robot arm according to the predetermined position. The test was 100% successful in carrying out all the movements of moving the robot arm position, although improvements still need to be made so that the robot arm can function better in the future.